A voyage of discovery [electronic resource] : made under the orders of the Admiralty, in His Majesty's ships Isabella and Alexander, for the purpose of exploring Baffin's Bay, and enquiring into the probability of a north-west passage - Ross, John, Sir, 1777-1856. (London : Printed by Strahan and Spottiswoode . for Longman, Hurst, Rees, Orme, and Brown ., 1819)
Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 40400-40402. Includes publisher's list. "In two volumes. Vol. I." Electronic reproduction. Mode of access: Internet. 44